2010
DOI: 10.1073/pnas.1010849107
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary growth hormone network responses are sexually dimorphic and regulated by gonadal steroids in adulthood

Abstract: There are well-recognized sex differences in many pituitary endocrine axes, usually thought to be generated by gonadal steroid imprinting of the neuroendocrine hypothalamus. However, the recognition that growth hormone (GH) cells are arranged in functionally organized networks raises the possibility that the responses of the network are different in males and females. We studied this by directly monitoring the calcium responses to an identical GH-releasing hormone (GHRH) stimulus in populations of individual G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 62 publications
(80 reference statements)
1
64
0
2
Order By: Relevance
“…Cell shape and network topology are thus adapted to provide equal access of cells to vasculature within the context of the other and more abundant lineages that occupy the bulk of the gland. Whereas cell networks may serve an important role in endocrine function by the rapid exchange of signals, as shown for the GH cell network (6,7,14), their presence may also reflect the developmental program of organogenesis (Fig. 5C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell shape and network topology are thus adapted to provide equal access of cells to vasculature within the context of the other and more abundant lineages that occupy the bulk of the gland. Whereas cell networks may serve an important role in endocrine function by the rapid exchange of signals, as shown for the GH cell network (6,7,14), their presence may also reflect the developmental program of organogenesis (Fig. 5C).…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of homotypic GH cell networks extending throughout the pituitary has provided the structural basis to explain these types of interactions and differing responsiveness. Indeed, all GH cells of the pituitary maintain adherent junctions with each other to form an extensive cell network that allows extremely rapid exchange of signals between cells and the production of highly synchronized and high amplitude secretory response (6,7). The existence of this 3D web-like GH cell network was not suspected before on the basis of traditional of 2D histological analyses, particularly as GH cells account for the bulk of anterior pituitary cells.…”
mentioning
confidence: 99%
“…Therefore, the pulsatory patterns of Gh secretion, and not the transcriptional levels of gh, determine the levels of Gh in the plasma. Thus, gonadal steroids are the main factors that regulate the patterns of GH secretion (Sanchez-Cardenas et al 2010). It has also been reported that sex steroids and some neurotransmitters, such as dopamine and glutamate, regulate Gh levels in fish sera (Wong et al 2006, Canosa et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Profound gender differences exist in several aspects of the endocrine axes (Nishida et al 2005, Sanchez-Cardenas et al 2010. Thus, exploration of sexual dimorphic expression of the major hormones in the pituitary gland may help to understand the physiological regulation of growth metabolism in adult fish.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analyses were performed using a Pearson R coefficient as previously detailed (72). Briefly, individual fluo-2-loaded cells were identified using a region of interest (ROI), and intensity over time traces and Cartesian (x-y) coordinates were extracted.…”
mentioning
confidence: 99%